Midlevel visual deficits after strokes involving area human V4. (January 2021) - Spang, Karoline; Grimsen, Cathleen; Prass, Maren; Brunner, Freimuth; Köhnlein, Martin; Kehrer, Stefanie; Kraft, Antje; Brandt, Stephan A.; Fahle, Manfred
Abstract: We present the results of 51 stroke patients with free central visual fields of which about half suffer from clear deficits of midlevel vision undetected by standard clinical tests. These patients yield significantly elevated thresholds for detection and/or discrimination between forms defined by motion, colour, or line orientation ('texture'). As demonstrated by voxel-based lesion-symptom mapping (VLSM) the underlying lesions involve mainly area human V4 (hV4) located in the posterior third of the fusiform gyrus and extending into the lingual gyrus. Patient's detection thresholds correlate only very weakly between the submodalities tested, indicating partly separate neural networks on mid-level vision for colour, motion, and texture detection. Correlations are far stronger for form discrimination tasks, indicating partly shared mechanisms for even simple form discrimination of distinct visual submodalities. We conclude that deficits of visual perception are far more common after strokes in visual brain areas than is apparent in clinical practice. Our results further clarify the functional organization of midlevel visual cortical areas.